Towards a legal framework for preventing tax revenue leakage in the upstream oil and gas industry in Tanzania: an analysis of the concepts, methods and options available in a public trusteeship model of natural resource holding - Luhende, Boniphace (Department of Commercial Law, 2018)
The recent discoveries of natural gas in Tanzania, estimated at about fifty-seven trillion cubic feet (tcf), have sparked tremendous hopes for socio-economic development in the country. While this optimism seems to be supported by conventional wisdom and economic insights, evidence from other oil-rich African countries shows that in spite of the ongoing oil and gas extraction, they are floundering in poverty, corruption and political instability. This phenomenal dichotomy between oil and gas wealth and socioeconomic development is referred to as the "resource curse". As this study demonstrates, the "curse" is partly a result of under-taxation. This study uses the resource curse study to analyze and evaluate tax-related challenges in the Tanzanian upstream oil and gas industry. In doing so, the study identifies three factors that may cause loss of potential tax revenues - referred to as "tax revenue leakage". First, the discretionary tax incentives, such as tax exemptions, lowering tax rates and special tax treatment, result in non-payment of taxes that would have otherwise been payable. Second, the International Oil Companies (IOCs) adopt a variety of techniques, such as transfer pricing, thin capitalization, corporate re-organization tax evasion and treaty shopping to exploit the loopholes or gaps in the tax laws to minimize, reduce or eliminate their tax obligations without being detected or punished. Third, corrupt Government officials willfully fail to collect taxes due, short levy taxes, grant undeserving tax incentives to the IOCs or divert revenues collected for their own account. All these factors demonstrate the close connection between under-taxation, corruption and tax avoidance. As this study argues, in the absence of counteractive measures, the Government will collect only a fraction of potential taxes, thus losing revenues required to finance development projects. The study establishes that Tanzania counteracts tax avoidance and tax evasion through anti-avoidance legislation. Tanzania also has accountability measures, which impose restraints on the exercise of public power and prevent corruption. The study concludes that although Tanzania has a competitive fiscal regime, anti-avoidance legislation and systems of accountability, the level of Government's tax revenue nevertheless depends on institutional capacity to detect, prevent and penalize tax avoidance schemes and corruption.